Odpowiedzi

2010-03-28T22:26:26+02:00
A) 3x-12-8x+28=2x+10
-5x+16=2x+10
-7x=-6
x=0,9
b)4x-6+12-3x=-x-1
x+6=-x-1
2x=-7
x=-3,5
c)2x-6-12-4x=-3x-6-4x-2
-2x-18=-7x-8
5x=10
x=2
d)6x+6+6-3x=4x-2-4+x
3x+12=5x-6
2x=-18
x=-9
e)2x+8-5x-15=2
-3x-7=2
-3x=9
x=-3
raczej dobrze :))
2010-03-28T22:33:42+02:00
A)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x=10+12-28
-7x=-6 /:(-7)
x=6/7

b)2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
4x-3x+x=-1+6-12
2x=-7 /:2
x=-3,5

c)2(X-3)-4(3+X)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-6-2+6+12
-3x=10 /:(-3)
x=-3/10

d)6(X+1)+3(2-X)=2(2X-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-12
-2x=-18 /: (-2)
x= 9

e)2(x+4)-5(x+3)=2
2x+8-5x-15=2
2x-5x=2-8+15
-3x=9 /:(-3)
x=-3

Pozdrawiam ;)
jestem pewna, że równania rozwiązałam dobrze, sprawdzałam kilka razy.



1 5 1